(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the clinical characteristics and early outcomes of laparoscopic gastrectomy combined with D2 lymph node dissection at 30-4 Hospital. Methods: A descriptive case series study was conducted on 37 patients diagnosed with gastric adenocarcinoma (stages I-III) from January 2022 to December 2024. Results: The rate of successful laparoscopic completion reached 100%, with no intraoperative mortality. The rate of severe complications requiring re-intervention was 0%. Except for 1 mortality case (2.7%) due to poor resuscitation response in an elderly patient with complex underlying comorbidities, all other cases achieved early recovery with very favorable clinical progress. Conclusion: Laparoscopic gastrectomy with D2 lymph node dissection is a safe, feasible, and effective procedure for the treatment of gastric cancer.